Gene Duplication to Reveal Adaptation Clue of Plant to Environmental Stress: A Case Study of NBS-LRR Genes in Soybean - Puji Lestari; Suk-Ha Lee; I Made Tasma; Asadi Asadi (Jurnal AgroBiogen, 2016)
Gene duplication to reveal adaptation clue of plant to environmental stress: A case study of NBS-LRR genes in soybean. Puji Lestari, Suk-Ha Lee, I Made Tasma, and Asadi. Adaptive strategies of plant to stress are fine-tuned by adjusting several activities including molecular mechanism which involve duplicated genes responsive to environmental changes. Genes responsive to the environmental stresses which are retained after small scale duplication are part of plant genome duplication. However, less information of duplicated genes could be adaptive to environmental changes in plant. This review presents an overview of duplication events in plant genomes which impact to gene duplication in relation to environmental changes, gene duplication as an adaptation mechanism, a case of duplicated nucleotide binding site-leucine-rich repeat (NBS-LRR) genes in soybean, and the gene duplication implementation for plant breeding in Indonesia. Notably, genome duplication events generate gene duplication and contribute to adaptive evolution against environmental changes. Generalization of plants to adapt the stressful conditions also probably improves our understanding of gene duplication as a mechanism of adaptation. Several recently duplicated NBS-LRR genes in soybean retain disease resistance QTL and the differential expression convince their contribution to biotic stress resistance in soybean. Proposed models of NBS-LRR genes duplication process may help to understand these genes response to the environmental changes. The duplication of genes resistant to pest/disease particularly NBS-LRR provides important information to select breeding parents and develop molecular markers related to desease resistance to genetically improve soybean in Indonesia. Overall, it may therefore be possible to enhance breeding which targets on genes tolerance/resistance to abiotic/biotic stress, and provide a molecular basis for crop-stress protection strategy and more improved soybean varieties specified for harsh environment.